Pengaruh Konten Instagram Aqua Terhadap Brand Image : Survei Pada Followers Instagram @sehataqua - Fadillah Aulia Latief Sultoni; Oktaviana Purnamasari (STIKes Ibnu Sina Ajibarang, 2024)
Nowadays, marketing is a systematic point that is very important for the success of a business in a company and also a company because of the increasingly fierce competition. The local brand of quality mineral water and also has a brandimage that is already embedded in the minds of consumers is Aqua. Brand image plays an important role in shaping brand image in the eyes of consumers and can influence the extent to which customers trust, recognize, and choose brands among their competitors. Instagram plays an important role in shaping brand image for businesses and brands. By using this platform to share creative, inspiring, and relevant content, companies can form an image on the brand that is positive and attractive to a wide audience or audience. The existence of this research has the aim of knowing how strong the influence of Aqua's Instagram content on brand image. The theory used in this research is Instagram content which consists of follow, like, comment, caption. Then next is the Brand Image theory which consists of the strength of brand association, the superiority of brand association, and the uniqueness of brand association on variables. The approach in this study is a quantitative approach with a survey method conducted on 79 respondents of @sehataqua Instagram followers, with sampling techniques using simple random sampling method. The results in the study indicate a fairly high influence, which is spelled out by the amount of 61% of Aqua's Instagram content on Brand image. While the remaining 39% is influenced by variables not examined in this study.